TURBINECTOMY VERSUS SUB-MUCOSAL DIATHERMY FOR TREATMENT OF HYPERTROPHIC TURBINATE - Muhammad Saleem; Muhammad Naeem; Sajjad Hyder et al. (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVE: To determine the efficacy of turbinectomy versus sub-mucosal diathermy for treatment of hypertrophic turbinates. STUDY DESIGN: Randomized controlled trial. PLACE AND DURATION OF STUDY: Ent Unit-1, Allied Hospital Faisalabad, Punjab Medical College, Faisalabad, From 01-04-2009 To 30-09-2009. METHODOLOGY: In order to compare the two techniques i.e. inferior turbinectomy and S.M.D, we divided the 92 patients into two groups A and B. Group A- turbinectomy and group-B for S.M.D. Pre-operative assessment was done for nasal obstruction in both groups A and B. Then two techniques were applied and postoperative evaluation in terms of improvement in nasal airflow after 48 hours and two weeks for both right and left sides were assessed. The results were compared of both techniques for the improvement in nasal obstruction. RESULTS: 42/46 group A patients having the overall improvement i.e. about 91.3 % after two weeks post-operatively. 36/46 group-B patients having the overall improvement which was about 78.3 %. The age range in both groups was 17 to 44 years and males in group-A were 36/46 and females were 10/46. In group-B males were 30/46 and females were 16/46. CONCLUSION: The group-A patients after two weeks post-operatively have better improvement in nasal obstruction as compared to group-B.